2013
DOI: 10.1002/jgrc.20069
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal Kelvin wave in Makassar Strait

Abstract: [1] Time series observations during [2004][2005][2006] reveal the presence of 60-90 days intraseasonal events that impact the transport and mixing environment within Makassar Strait. The observed velocity and temperature fluctuations within the pycnocline reveal the presence of Kelvin waves including vertical energy propagation, energy equipartition, and nondispersive relationship. Two current meters at 750 and 1500 m provide further evidence that the vertical structure of the downwelling Kelvin wave resembles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
51
0
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 25 publications
7
51
0
6
Order By: Relevance
“…From the semiannual amplitudes in the different seas, it is inferred that the waves propagate to the shallower Java Sea reaching the Makassar Strait, but do not influence the variability of the deeper Flores and Banda basins. This is in agreement with previous studies that concluded that the Kelvin waves exiting the Lombok Strait travel along the 100-m isobath (Pujiana et al, 2013).…”
Section: Indonesian Seassupporting
confidence: 93%
“…From the semiannual amplitudes in the different seas, it is inferred that the waves propagate to the shallower Java Sea reaching the Makassar Strait, but do not influence the variability of the deeper Flores and Banda basins. This is in agreement with previous studies that concluded that the Kelvin waves exiting the Lombok Strait travel along the 100-m isobath (Pujiana et al, 2013).…”
Section: Indonesian Seassupporting
confidence: 93%
“…Fluktuasi transpor APJS dalam skala ISV yang sering muncul dalam periode transisi yang terungkap dalam kajian ini, adalah cukup konsisten dengan kajian sebelumnya mengenai variabilitas arus di kawasan Selatan Jawa (misalnya Iskandar et al, 2005;Sprintall et al, 2009). Variabilitas transpor APJS dalam skala ISV di Selatan Jawa dibangkitkan oleh remote forcing gelombang Kelvin ekuator Samudera Hindia yang merambat di sepanjang Barat Sumatera -Selatan Jawa, dimana intrusi gelombang Kelvin ke Selat Lombok ini dapat mempengaruhi Arlindo Lombok dalam skala ISV (Arief dan Murray 1996;Qiu et al 1999;Pujiana et al, 2013).…”
Section: Variabilitas Transpor Arlindounclassified
“…sebelumnya (Sprintall et al, 2001;Syamsudin et al, 2004;Pujiana et al, 2013). Angin zonal di tengah ekuator Samudera Hindia (70-90 °BT) besaran kecepatannya terjadi lonjakan yang drastis ke arah timur (westerly winds bursts) dalam periode musim Transisi 1 (Maret-Mei) dan musim Transisi 2 (September-November).…”
Section: Variabilitas Transpor Arlindounclassified
“…Jika melihat adanya variasi kekuatan arus pada kedalaman di bawah piknoklin, maka dapat diduga adanya shear stress aliran ITF berpotensi memicu ketidakstabilan (instability). Kondisi arus pada November 2006 (tidak ditampilkan) menunjukkan arah aliran ITF berbalik ke utara pada kedalaman 350 m. Instability oleh shear dapat ditunjukkan oleh nilai Richardson number, Ri = N 2 /shear 2 , yang lebih kecil dari 0,25, tetapi nilai ini tidak merefeksikan mekanisme yang melatarbelakangi percampuran turbulen tersebut (Depleche et al, 2010 Kemungkinan pemicu lain proses percampuran turbulen di S. Makassar adalah gelombang Kelvin (Pujiana et al, 2013 …”
Section: Kekuatan Percampuran Turbulenunclassified